2018 7th IEEE International Conference on Biomedical Robotics and Biomechatronics (Biorob) 2018
DOI: 10.1109/biorob.2018.8487616
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Forward Fall on the Outstretched Hand Using MADYMO Human Body Model

Abstract: Falls and their related injuries pose a significant risk to human health. One of the most common falls, the forward fall, frequently occurs among adults and the elderly. In this study, we propose using a human body model, developed using the MAthematical DYnamic MOdel (MADYMO) software, in place of human subjects, to investigate forward fall-related injuries. The MADYMO human body model is capable of simulating items that cannot be assessed on human subjects, such as human kinematics, human dynamics, and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Several groups have employed a range of computational approaches in trying to determine internal tissue loading corresponding to fall events including finite element models, 53 , 54 spring-mass-damper lumped force models, 55 and rigid body dynamic simulations. 18 , 30 , 56 Each approach provides insights into tissue loading and injury risk; however, we are becoming increasingly aware of the need for these models to capture individual variability instead of a single generic computational model to accurately capture tissue mechanics. In this study, we found that default joint stiffness values for the human models needed to be scaled from 0.87 to 3.28 times the original values in order to match each fall’s kinematics.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have employed a range of computational approaches in trying to determine internal tissue loading corresponding to fall events including finite element models, 53 , 54 spring-mass-damper lumped force models, 55 and rigid body dynamic simulations. 18 , 30 , 56 Each approach provides insights into tissue loading and injury risk; however, we are becoming increasingly aware of the need for these models to capture individual variability instead of a single generic computational model to accurately capture tissue mechanics. In this study, we found that default joint stiffness values for the human models needed to be scaled from 0.87 to 3.28 times the original values in order to match each fall’s kinematics.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental results provided in this study provide valuable calibration and validation data for computational models of falls onto outstretched hands [ 94 ] In rigid-body dynamics simulations of falls, modelers use tissue properties to describe impacts between the body and other objects [ 95 , 96 ]. The energy absorbed found in this study could help to validate the hysteresis response of the tissue which is important for quantifying the degree of elasticity or inelasticity in the impact.…”
Section: Discussionmentioning
confidence: 99%
“…Fracture risk of the wrist depends on the magnitude and distribution of forces applied to the palmar surface and on the soft tissue response of the palm [10][11][12][13]. Increasingly, computational models [14][15][16] and crash test dummies [17][18][19][20] are being used to simulate falls to quantify impact mechanics and define injury risk; however, these models are limited by a lack of accurate soft tissue properties. Characterizing the in vivo response of the palmar soft tissue will help us better simulate fall mechanics, quantify injury risk and identify opportunities for injury prevention.…”
Section: Introductionmentioning
confidence: 99%
“…27,29,30 For fall events, impact velocity and impact location were determined using video of the event from sport and through full-body computer simulation using MADYMO software to estimate the fall mechanics likely to have occurred from the medical report descriptions. 5,10,27,2933 The characteristics for each of the 72 significant head impact cases are described per impact event in Table 1. This table provides a summary of the impact velocities, impact masses, and compliance for each of the different impact events.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, collisions typically involve a padded shoulder or elbow impact to the helmeted head where both the striking object and struck object have protective layers and are free to move post-impact. 3,[6][7][8][9][10] Ice hockey is also unique in that fighting at the junior and professional levels is common where fighting increases the likelihood of concussive injuries. 2 Combative sports, such as boxing and mixed-martial arts (MMAs), with the goal of delivering "knockout" blows to their opponent, are also highrisk sports for concussive injury.…”
Section: Introductionmentioning
confidence: 99%